2017
DOI: 10.1002/2017gl073531
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling anthropogenic influence on the changing risk of heat waves in China

Abstract: Heat waves trigger substantial social and environmental impacts and even cause massive civilian casualties in extreme cases. Observations show the areas affected by heat waves have increased over China, with the most extreme heat wave occurring during the past five decades. Here we show that both trends can be attributed to anthropogenic influences. We report that under the moderate Representative Concentration Pathways 4.5 scenario, anthropogenic influences will increase the risk of occurrence of the observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 33 publications
3
34
0
Order By: Relevance
“…Q. Sun et al (2017) examined anthropogenic influence on the probability of extreme heat waves in China. They found that the likelihood of the strongest heat wave in observational record recurring across more than half China would increase by tenfold in the late 21st century under the moderate Representative Concentration Pathway 4.5 scenario (Stocker et al, 2013).…”
Section: 1029/2018ef000963mentioning
confidence: 99%
See 1 more Smart Citation
“…Q. Sun et al (2017) examined anthropogenic influence on the probability of extreme heat waves in China. They found that the likelihood of the strongest heat wave in observational record recurring across more than half China would increase by tenfold in the late 21st century under the moderate Representative Concentration Pathway 4.5 scenario (Stocker et al, 2013).…”
Section: 1029/2018ef000963mentioning
confidence: 99%
“…The warming observed in China can be attributed to human-induced emission of greenhouse gases (Lu et al, 2016;Yin et al, 2017), exacerbated by urbanization (Y. Sun et al (2017) examined anthropogenic influence on the probability of extreme heat waves in China. As warming is projected to continue (Stocker et al, 2013) and irreversible (Solomon et al, 2009), it is important to understand how heat waves may change in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The climate in eastern China is dominated by the East Asian Summer monsoon and often characterized by a wet and warm summer season (Ding and Chan 2005). This region is home to a large portion of the Chinese population and is frequently struck by heat extremes (Li et al 2014, Sun et al 2014, Sun et al 2017. Thus, improving extreme weather forecast over eastern China would be of great socioeconomic significance.…”
Section: Introductionmentioning
confidence: 99%
“…This raises interests on the effects of human‐induced climate change and natural variability on the occurrence of extreme hot events and to what extent they will increase in the future as human activities continue. Analyses based on a probabilistic attribution framework suggest that combined effects of human activities and natural variability could explain the occurrence of a heatwave event, while anthropogenic emissions of greenhouse gases have increased the frequency and likelihood of most heatwaves (Miao et al, 2016; Otto et al, 2012; Perkins et al, 2014; Sun et al, 2014; Sun et al, 2017; Wang et al, 2019). For example, midsummer of 2013 heat event in Central and Eastern China was impacted by both anthropogenic factors and atmospheric natural variability, while anthropogenic influence caused more than fourfold increase in the likelihood of such extremely high temperature events (Ma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%